Epidemiology of bloodstream Candida species in a Spanish tertiary care hospital as a guide for implementation of T2MR (T2CANDIDA®) for rapid diagnosis of candidemia. (7th July 2020) - Falces-Romero, Iker; Romero-Gómez, María Pilar; Moreno-Ramos, Francisco; Mingorance, Jesús; García-Rodríguez, Julio; Cendejas-Bueno, Emilio
Abstract: The aim of this work was to study the epidemiology of candidemia in our hospital in order to determine whether the T2MR system might be a useful tool for early diagnosis of candidemia in selected units. We perform a retrospective review of all candidemia episodes registered in the last 12 years in selected units of our hospital in adult and pediatric patients. Candida species and antifungal susceptibility patterns were registered. A total of 686 isolates were registered, of which 625 were infections due to the five most common species of Candida. C. albicans (45.6%) and C. parapsilosis (33.1%) were the predominant species found in our institution. In adults these species were closely followed by C. glabrata (12–21%) in all units. While in pediatric medical and intensive care units (PICU), these species were followed by other uncommon yeasts. Resistance rates to triazoles were low in C. albicans and C. parapsilosis . In C. glabrata and C. tropicalis the resistance rates to fluconazole ranged from 10.86 to 6.67%. Resistance rates for echinocandins were very low and all strains were susceptible to amphotericin B. T2Candida ® might be useful to guide antifungal targeted treatment and discontinuation of antifungal empirical treatment in those units where the five most common Candida species represent more than the ninety percent of the isolates. The selection of medical and surgical units should be based on local epidemiology and antifungal susceptibility patterns. Incidence should be taken into account in order to make clinical decisions based on negative results. Lay Abstract: T2Candida ® might be useful selectively in clinical units according to their local epidemiology, antifungal resistance patterns, and incidence of candidemia. It optimizes the clinical value of positive results supporting decisions about targeted therapies or discontinuations based on negative results.